Reworking of Archean mantle in the NE Siberian craton by carbonatite and silicate melt metasomatism: Evidence from a carbonate-bearing, dunite-to-websterite xenolith suite from the Obnazhennaya kimberlite - Ionov, D.; Doucet, Luc; Xu, Y.; Golovin, A.; Oleinikov, O. (Pergamon, 2018)
The Obnazhennaya kimberlite in the NE Siberian craton hosts a most unusual cratonic xenolith suite, with common rocks rich in pyroxenes and garnet, and no sheared peridotites. We report petrographic and chemical data for whole rocks (WR) and minerals of 20 spinel and garnet peridotites from Obnazhennaya with Re-depletion Os isotope ages of 1.8–2.9 Ga (Ionov et al., 2015a) as well as 2 pyroxenites. The garnet-bearing rocks equilibrated at 1.6–2.8 GPa and 710–1050 °C. Some xenoliths contain vermicular spinel-pyroxene aggregates with REE patterns in clinopyroxene mimicking those of garnet. The peridotites show significant scatter of Mg# (0.888–0.924), Cr2O3 (0.2–1.4 wt.%) and high NiO (0.3–0.4 wt.%). None are pristine melting residues. Low-CaO-Al2O3 (≤0.9 wt.%) dunites and harzburgites are melt-channel materials. Peridotites with low to moderate Al2O3 (0.4–1.8 wt.%) usually have CaO > Al2O3, and some have pockets of calcite texturally equilibrated with olivine and garnet. Such carbonates, exceptional in mantle xenoliths and reported here for the first time for the Siberian mantle, provide direct evidence for modal makeover and Ca and LREE enrichments by ephemeral carbonate-rich melts. Peridotites rich in CaO and Al2O3 (2.7–8.0 wt.%) formed by reaction with silicate melts.